The "how" and "why" of the ancient Greek long jump with weights: A five-fold symmetric jump in a row? - Lenoir, M.; de Clercq, D.; Laporte, W. (Journal of Sports Sciences, 2005)
A plausible explanation for the ancient long jump records from Greek antiquity is sought on the basis of pictorial and written sources, and corroborated with practical tests. Ancient sources report that athletes jumped more than 15m with weights in their hands, which enabled them to jump further than without these weights. It is proposed that the ancient Greek long jump was a continuous succession of five standing broad jumps, in which the landing phase of one jump was also the countermovement for the next jump. Four trained athletes jumped further with (14.64±0.76m, range 13.64-15.63m) than without weights (13.88±0.70m, range 12.60-14.75m; P=0.001). These results show that this technique is executable, fits with ancient written and pictorial sources, and allows trained modern athletes to jump distances well over 15m. The extra distance jumped when using weights may be due to changes in the position of the jumper's centre of mass at take-off and at landing, and an increase in take-off velocity stemming from several biomechanical mechanisms.